Stiffness Analysis of Rectangular Isolators Reinforced by Engineering Plastics - Han Liu; Ping Tan; Fulin Zhou (Shock and Vibration)
A novel cost-effective isolator reinforced by engineering plastics has been designed and manufactured for seismic protection for low-rise buildings in less developed areas. The reinforcement is flexible in tension, which is similar to fiber-reinforced isolators. However, available solutions for fiber-reinforced isolators are not applicable, because the Poisson effect of engineering plastics cannot be neglected, which is done for fiber reinforcement. In this paper, analytical solutions for compression and bending stiffness for rectangular isolators reinforced by engineering plastics are proposed, with both the Poisson effect of the reinforcement and the effect of rubber compressibility taken into consideration. Then, the simplified solutions are also derived, which can greatly improve calculation efficiency. To validate the solutions, finite element analysis is conducted on a set of isolators with different reinforcement stiffnesses. The results show the superiority of the proposed solutions to the previous solutions for fiber-reinforced isolators. A series of experimental tests of the isolators are also carried out to verify the solutions. Both the analytical and the simplified solutions match well with the experimental results.